the quadratic formula is derived by completing the square
in other words, by using the quadratic formula, you do complete the square but you skip straight to the answer
below is the derivation of the quadratic formula just for fun
note: I used the method of completing the square to derive the formula
ax²+bx+c=0
group like terms
(ax²+bx)+c=0
factor out quadratic coefient
![a(x^2+(b)/(a)x)+c=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/tl8veoz2c2jwspyn4tlzq1ktrpybm4s7fi.png)
take 1/2 of linear coefient and square it
(b/a)/2=b/(2a), ((b/(2a))^2=(b^2)/(4a^2)
add positive and negative of it inside parntheasees
![a(x^2+(b)/(a)x+(b^2)/(4a^2)-(b^2)/(4a^2))+c=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/oh7821740l9i2dpjy2uu1z5vl35rw4ls05.png)
factor perfect square trinomial
![a((x+(b)/(2a))^2-(b^2)/(4a^2))+c=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/dnnxd3707lf6jwazo5631um9ohsjmxuy39.png)
expand
![a(x+(b)/(2a))^2-(b^2)/(4a)+c=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/3w76mo45wjm5foy71b8d456apxuin43yqu.png)
add (b^2/4a-c) to both sides
![a(x+(b)/(2a))^2=(b^2)/(4a)-c](https://img.qammunity.org/2019/formulas/mathematics/high-school/e5v6ofs94mkw66ur2szhlgmvn7ajzm5cbb.png)
divide by both sides by a
![(x+(b)/(2a))^2=(b^2)/(4a^2)-(c)/(a)](https://img.qammunity.org/2019/formulas/mathematics/high-school/5cva604t0hf4z2ay7ien56dotb8wxnqqhh.png)
before we go on, combine right side into 1 fraction
(c/a)(4a/4a)=4ac/4a^2, so
![(b^2)/(4a^2)-(c)/(a)=(b^2-4ac)/(4a^2)](https://img.qammunity.org/2019/formulas/mathematics/high-school/yqmpo8i4uryk0det7tfresmdsb1t1ut7f5.png)
![(x+(b)/(2a))^2=(b^2-4ac)/(4a^2)](https://img.qammunity.org/2019/formulas/mathematics/high-school/iy2fng5vfft4bjsaex7ejmn6biyqzh18qj.png)
square root both sides
![x+(b)/(2a)=\pm \sqrt{(b^2-4ac)/(4a^2)}](https://img.qammunity.org/2019/formulas/mathematics/high-school/c4f7sv5faqh9eok23irvgjy4y4qyr2v0q2.png)
![x+(b)/(2a)=(\pm √(b^2-4ac))/(2a)](https://img.qammunity.org/2019/formulas/mathematics/high-school/zu5313ji0wfx2qj6uymh6qv6ok1x62f2vz.png)
subtract
from both sides
![x=(-b \pm √(b^2-4ac))/(2a)](https://img.qammunity.org/2019/formulas/mathematics/college/lihe8yiveea681tnmlt7bwz1aygq2wqx11.png)
in conclusion, the quadratic formula completes the square for you and is therefore faster when you are given the function in standard form (0=ax²+bx+c).